PENGELOLAAN PERIKANAN HIU DI PELABUHAN PERIKANAN PANTAI TEGALSARI TEGAL - Septiawan, Heppy; Primasari, Bayu (Jurnal Teknologi Perikanan dan Kelautan, 2023)
A Sharks is a type of cartilaginous fish (Elasmobranchii) that act as a top predator in the food chain and also has an important role in maintaining the balance of oceanic ecosystems. Currently, sharks are threatened with extinction due to overfishing activities caused by the increasing demand for fin commodities on the international market. One of the landing bases for shark catches in Indonesia is located at Tegalsari Beach Fishing Port (PPP) in Tegal City, Central Java Province. The pressure on shark populations in this area comes not only from an increase in fishing effort, but also from water and habitat degradations. This study aimed to analyze the performance of shark fisheries management in Tegalsari PPP using the Ecosystem Approach to Fisheries Management (EAFM) approach and develop recommendations for management actions. The results showed that the performance of shark fisheries management at PPP Tegalsari was in a good condition with an overall average domain score of 73.39. Management actions were prioritized in the economic and fish resource domains, namely business diversification and simplification access to capital for household fishery, making regulations limiting fishing effort and the minimum size of sharks that can be caught; and increasing supervision related to selectivity of fishing gear and fishing methods.